Variables Affecting In-Vitro Evaluation of Loxoprofen Sodium Topical Emulgel - Zainab H. Mahdi; Suhail, Aseel; Khazaal Maraie, Nidhal; Huda S. Kathem (Iraqi Journal of Pharmaceutical Sciences, 2024)
Although topical preparations like creams, ointments, and gels were used for many years to achieve local or sometimes systemic effects, they have many limitations mostly the inability to control the release of medications. In this research, a new emulgel preparation of loxoprofen sodium was formulated as a suitable alternative possessing the properties of both emulsion and gel preparation making it suitable to prolong the release of the hydrophilic drug. For this reason, five different emulgel formulas were prepared using different percentages of liquid paraffin (5%,10%), tween 80 & span 80 emulsifier mixture (2.5%, 5%), and xanthan gum (1%, 2%). The formulations were evaluated for their physicochemical, rheological, and spreading properties, in addition to content uniformity and in-vitro release properties. Furthermore, the optimum selected emulgel formula was subjected to a skin irritation test, stability, and compatibility study besides an in-vitro release comparison with the marketed Loxonin® gel. The result of all formulated emulgels showed excellent homogeneity, consistency with no phase separation and accepted pH (6.12±0.76 to 6.51±0.92), and content uniformity (99.02±0.45 to 99.48±1.49). Moreover, all the formulas showed a thixotropic shear-thinning behavior with the optimum formula F3 exhibiting the highest spreadability value of (8.3±0.1 cm), and the highest extent of drug liberated after 6 hours (94.81±1.30 %). Additionally, the selected loxoprofen emulgel F3 showed no irritation to human skin, and no significant change upon storage at 4±2°C and 25±2°C with acceptable compatibility. Eventually, the selected formula displayed a slower rate of loxoprofen release than the marketed gel, a result that proves the effectiveness of the newly formulated loxoprofen emulgel for a prolonged release giving better patient compliance.